Dynamic Reflexivity in Action: An Armchair Walkthrough of a Qualitatively Driven Mixed-Method and Multiple Methods Study of Mindfulness Training in Schoolchildren. (June 2015) - Cheek, Julianne; Lipschitz, David L.; Abrams, Elizabeth M.; Vago, David R.; Nakamura, Yoshio
Dynamic reflexivity is central to enabling flexible and emergent qualitatively driven inductive mixed-method and multiple methods research designs. Yet too often, such reflexivity, and how it is used at various points of a study, is absent when we write our research reports. Instead, reports of mixed-method and multiple methods research focus on what was done rather than how it came to be done. This article seeks to redress this absence of emphasis on the reflexive thinking underpinning the way that mixed- and multiple methods, qualitatively driven research approaches are thought about and subsequently used throughout a project. Using Morse's notion of an armchair walkthrough, we excavate and explore the layers of decisions we made about how, and why, to use qualitatively driven mixed-method and multiple methods research in a study of mindfulness training (MT) in schoolchildren.